2011
DOI: 10.1165/rcmb.2009-0445oc
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effects of Thiazolidinediones in Human Airway Smooth Muscle Cells

Abstract: Airway smooth muscle (ASM) cells have been reported to contribute to the inflammation of asthma. Because the thiazolidinediones (TZDs) exert anti-inflammatory effects, we examined the effects of troglitazone and rosiglitazone on the release of inflammatory moieties from cultured human ASM cells. Troglitazone dosedependently reduced the IL-1b-induced release of IL-6 and vascular endothelial growth factor, the TNF-a-induced release of eotaxin and regulated on activation, normal T expressed and secreted (RANTES),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 80 publications
(84 reference statements)
3
31
0
Order By: Relevance
“…26 Conversely, in other experiments, BADGE and GW9662 did not antagonize PPARγ signaling nor prevent adipogenesis in vitro and in vivo. [27][28][29][30] In one study, BADGE actually promoted adipogenesis at nanomolar levels, while higher concentrations of BADGE were cytotoxic. 28 We found that low dose BADGE had either no therapeutic effect or even worsened BM failure, whereas high dose BADGE did not add to hematological improvement.…”
Section: Discussionmentioning
confidence: 99%
“…26 Conversely, in other experiments, BADGE and GW9662 did not antagonize PPARγ signaling nor prevent adipogenesis in vitro and in vivo. [27][28][29][30] In one study, BADGE actually promoted adipogenesis at nanomolar levels, while higher concentrations of BADGE were cytotoxic. 28 We found that low dose BADGE had either no therapeutic effect or even worsened BM failure, whereas high dose BADGE did not add to hematological improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PPARγ agonists also vasodilate both pre- and postglomerular arterioles that decrease the glomerular capillary pressure (P GC ) [13] allowing the reduction in glomerular hyperfiltration and albumin excretion when used in diabetic patients [3]. However, the use of PPARγ agonists is not restricted to diabetic patients due to its anti-inflammatory action [2,9,10]. Thus, the reduction in P GC may diminish GFR and blood supply to tubular epithelial cells predisposing non-diabetic patients using PPARγ agonists to renal ischemia and AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the European Medicines Agency suspended RGL from the European market since September 2010. Despite well documented side effects, many other studies continue to indicate the use of RGL in diabetic and nondiabetic patients due to its anti-inflammatory property [9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…In vitro, human ASM cytokine secretion and proliferation have been shown to be suppressed by the PPAR␥ agonists RGZ and ciglitazone (CGZ) (10,27,30,34,37). However, only some of these anti-inflammatory and antiremodeling activities were inhibited by the selective PPAR␥ antagonist GW9662, suggesting both PPAR␥-dependent and -independent mechanisms (30, 34).…”
mentioning
confidence: 99%